STRATEGI KOMUNIKASI PERSUASIF KEPALA SEKOLAH DALAM MENCEGAH TAWURAN ANTAR PELAJAR MENENGAH KEGURUAN AL-WASHLIYAH 4 MEDAN - Nasution, Cucu Cahaya Hati; Harahap, Muhammad Said (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
This research aims to investigate and analyze the persuasive communication strategies implemented by the School Principal in preventing student conflicts at Al-Washliyah 4 Vocational High School in Medan. Student conflicts are a significant issue within the school environment, requiring an effective approach to prevent and address conflicts among students. The research methodology employed is qualitative, involving interviews with the School Principal and direct observation of the implementation of persuasive communication strategies. Data analysis is conducted using a qualitative approach, focusing on the identification of persuasive elements applied and their impact on student behavior. The research results are expected to provide profound insights into the effectiveness of persuasive communication strategies in preventing student conflicts. The practical implications of this research can be used as a foundation for improving the strategies that have been implemented and contribute to the literature on persuasive communication strategies in an educational context. Therefore, this research is expected to make a positive contribution to conflict prevention efforts in the school environment and the overall enhancement of education quality.